Determining Surface Tension of Liquids: Molecular Mechanisms and Practical Applications - Warsih, Dewinta; Konit Istiqomah, Ikmal; Malik, Adam; Dewi Salsabila, Luthfiah (UIN Alauddin Makassar, 2024)
This study aims to explain the molecular mechanisms controlling the surface tension of liquids and determine the magnitude of the surface tension of liquids. The research was conducted through laboratory experiments with variations in temperature and the addition of surfactants. Data was collected by dipping the device into soapy water and measuring the changes in string tension before and after immersion. The results showed that the surface tension of hot soapy water is lower than that of cold soapy water. This reduction in surface tension is due to the increased kinetic energy of molecules at higher temperatures. These findings are relevant in various scientific and industrial applications, including capillarity in plants, industrial cleaning, and understanding the hydrological cycle. This research provides a deeper understanding of surface tension and its implications in everyday life.